Histopathological Examination of Gallbladder in Cholecystectomy Specimens in Lumbini Medical College and Teaching Hospital - Laxmi Lama; Gubhaju , Manisha Bajracharya; Shrestha, Dipesh; Gubhaju, Prasamsha Bajracharya (Nepal Journal of Health Sciences, 2026)
Background: More than 95% of biliary tract infection is caused by Gallstone. Cholecystectomy, the utmost major abdominal operation across the globe. Cholelithiasis establish a numerous histopathologic variation in gallbladder mucosa, which is acute and chronic inflammation, cholesterolosis, hyperplasia, granulomatous inflammation, dysplasia, carcinoma in situ and carcinoma. Methodology: This was a retrospective study of 200 cholecystectomy specimens received in the Department of Pathology, Lumbini Medical College and Teaching Hospital (LMC-TH) over a period of 2.5 years from 2022 to 2025. Clinical details and histopathological data were retrieved from the records file. A wide variety of histomorphological changes in the resected gall bladder was studied. Result: Out of 200 cases, 134 (67%) were female and male 66 (33%), with male to female ratio was 1:2. Also the patients age ranged from 8 years to 85 years with mean age of 46.75±14.202 years. Histopathological examination showed chronic cholecystitis was the most usual findings (50%) with a female predominance. The least common variant was Adenocarcinoma NOS, low-grade dysplasia and empyema of the gallbladder each in 1% of cases. Analysis of the relationship between serosal and age of the respondants using the chi-square test yielded P-value of 0.024, indicating significant association. The significant association was observed between sex of the respondents with serosal surface, whereas age of respondents was not found to be significantly associated with serosal surface. Conclusion: To identify the non-neoplastic lesion along with its complication and incidental gallbladder carcinoma in cholecystectomy specimens is crucial during routine histopathological examination.